Aborsi di Era Modernisasi dalam Pespektif Alkitab (Jurnal Pendidikan Agama dan Teologi, 2025)
This research analyzes the phenomenon of abortion in the context of modernization, emphasizing the Biblical perspective. Through a literature review and analysis of relevant Bible verses, this research aims to understand the Bible's view on abortion and its implications in an increasingly plural and complex modern society. This study will also explore how Biblical values ​​can provide an ethical basis for dealing with moral dilemmas related to abortion